Role of Diagnostic and Prognostic Immunohistochemical Markers in Hepatocellular Carcinoma: Prognostic Immunohistochemical Markers in Hepatocellular Carcinoma - Memon, Abdul Qayoom; Ashraf, Sarwat; Aziz, Asif; Phulpoto, Abdul Hayee; Pervez, Safdar Ali; Ramani, Ratan Kumar (Pakistan Journal of Health Sciences, 2025)
As the primary cause of cancer-related death globally, Hepatocellular Carcinoma requires accurate diagnostic and prognostic markers. Immunohistochemical indicators have been identified as promising instruments to improve the precision of hepatocellular Carcinoma diagnosis and forecast patient outcomes. Objectives: To evaluate the relationships between clinicopathological characteristics associated with hepatocellular carcinoma, such as tumor grade, vascular invasion, and patient characteristics, and the expression of immunohistochemical markers. Methods: A cross-sectional study was conducted for six months from Feb 2024 to Jul 2024 in the Department of Pathology at a tertiary care hospital. There were 323 patients with Hepatocellular Carcinoma diagnoses in all. Immunohistochemical was used to examine specimens of tissue for the markers Ki-67, CK19, Glypican-3, alpha-fetoprotein (AFP), HepPar-1, and CD34. Kaplan-Meier survival analysis, t-tests, and chi-square tests were used to evaluate correlation with clinicopathological characteristics and survival results. Results: High percentages of positive expression were seen for CD34 (88.2%), Glypican-3 (75.9%), and HepPar-1 (82.7%). There were noteworthy associations discovered between tumor size, vascular invasion, and serum AFP levels and IHC markers. Notably, HepPar-1 positive predicted a better prognosis (HR 0.72, p=0.032), but Glypican-3 (HR 1.58, p=0.001) and Ki-67 (HR 2.10, p=0.002) were linked to poor overall survival. Conclusions: It was concluded that the significant associations between specific immunohistochemical markers (e.g., HepPar-1, Glypican-3, and Ki-67) and clinicopathological characteristics, as well as their impact on prognosis in Hepatocellular Carcinoma patients.